2018
DOI: 10.1002/pbc.27265
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid lineage switch following chimeric antigen receptor T‐cell therapy in a patient with TCF3‐ZNF384 fusion‐positive B‐lymphoblastic leukemia

Abstract: A pediatric patient diagnosed initially with B-lymphoblastic leukemia (B-ALL) relapsed with lineage switch to acute myeloid leukemia (AML) after chimeric antigen receptor T-cell (CAR-T) therapy and hematopoietic stem cell transplant. A TCF3-ZNF384 fusion was identified at diagnosis, persisted through B-ALL relapse, and was also present in the AML relapse cell population. ZNF384-rearrangements define a molecular subtype of B-ALL characterized by a pro-B-cell immunophenotype; furthermore, ZNF384-rearrangements a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 12 publications
2
69
0
1
Order By: Relevance
“…Although there is hope for this strategy, leukemia has already figured out an escape plan for that as well -lineage switch. Some B cell leukemias can switch lineages, activating myeloid expression markers and suppressing lymphoid ones (including CD22) and this has been reported in CAR T cell therapy (15,16). Can we predict lineage switch and pre-empt it with transplantation, and will transplantation actually work for that purpose?…”
Section: Could Universal Car T Cells Be the Answer?mentioning
confidence: 95%
“…Although there is hope for this strategy, leukemia has already figured out an escape plan for that as well -lineage switch. Some B cell leukemias can switch lineages, activating myeloid expression markers and suppressing lymphoid ones (including CD22) and this has been reported in CAR T cell therapy (15,16). Can we predict lineage switch and pre-empt it with transplantation, and will transplantation actually work for that purpose?…”
Section: Could Universal Car T Cells Be the Answer?mentioning
confidence: 95%
“…It occurs more often in paediatric leukaemias, being reported mostly in patients with KMT2A rearrangement [6][7][8] but rarely also in patients with ZNF384-rearranged acute leukaemias. 5,9 The lineage switch mostly occurs at the time of relapse. However, it is also reported in patients who have received either CD19-targeting agents or chimeric antigen receptor T-cell therapy.…”
Section: Tcf3-znf384-rearranged Leukaemias Resembles Those With Kmt2amentioning
confidence: 99%
“…Primary T-cell failure Low memory/stem-cell memory T cells in the leukapheresis [21] Lack of multi-cytokine producing cells [22] Increased exhaustion of cells [21,[23][24][25]] Increased regulatory T cells [26] Secondary T-cell failure Nature of the costimulatory domain [27,28] Anti-CAR immune response [10,13] Suppressive microenvironment in extramedullary leukemia [15,29] Target Antigen Modulation Loss of CD19 expression Mutations in CD19 [30,31] Splice variants of CD19 [30] Lineage switch to myeloid leukemia [32][33][34][35] Defective trafficking to the cell membrane [36] Leukemia transduction by CAR masking CD19 expression [37] CD22 down modulation Unknown posttranscriptional effects [7] Abbreviation: CAR-T cells: chimeric-antigen receptor expressing T cells.…”
Section: T-cell Failure Production Failure Failure Of T-cell Expansiomentioning
confidence: 99%
“…A recent report from Novartis suggested that CD19 mutations, rarely seen before, accounted for the majority of CD19 non-expressing cases [31]. Several groups have reported lineage switch of leukemia to occur following CD19directed therapy, especially in cases where the leukemia cell of origin is not a precursor B-cell per se (such as MLL-rearranged leukemia) [32][33][34][35]. Unique mechanisms, such as defects in the CD81-CD19 co-trafficking from the endoplasmic reticulum to the cell surface [36], or co-transduction of leukemia with CAR-T cells thereby CAR-CD19 interactions occurring in cis and masking CD19 presentation from T cells [37], have also been reported.…”
Section: Target-antigen Modulationmentioning
confidence: 99%